Exploring the Usage of ChatGPT Among Medical Students in the United States - Janice S. Zhang; Christine Yoon; Darnell K. Adrian Williams; Adi Pinkas (Journal of Medical Education and Curricular Development, 2024)
OBJECTIVES Chat Generative Pretrained Transformer (ChatGPT) is a large language model developed by OpenAI that has gained widespread interest. It has been cited for its potential impact on health care and its beneficial role in medical education. However, there is limited investigation into its use among medical students. In this study, we evaluated the frequency of ChatGPT use, motivations for use, and preference for ChatGPT over existing resources among medical students in the United States. METHODS Data was collected from an original survey consisting of 14 questions assessing the frequency and usage of ChatGPT in various contexts within medical education. The survey was distributed via email lists, group messaging applications, and classroom lectures to medical students across the United States. Responses were collected between August and October 2023. RESULTS One hundred thirty-one participants completed the survey and were included in the analysis. Of the total, 48.9% respondents responded that they have used ChatGPT in medical studies. Among ChatGPT users, 43.7% of respondents report using ChatGPT weekly, several times per week, or daily. ChatGPT is most used for writing, revising, editing, and summarizing purposes. 37.5% and 41.3% of respondents reported using ChatGPT more than 25% of the working time for these tasks respectively. Among respondents who have not used ChatGPT, more than 50% of respondents reported they were extremely unlikely or unlikely to use ChatGPT across all surveyed scenarios. ChatGPT users report they are more likely to use ChatGPT over directly asking professors or attendings (45.3%), textbooks (42.2%), and lectures (31.7%), and least likely to be used over popular flashcard application Anki (11.1%) and medical education videos (9.5%). CONCLUSIONS ChatGPT is an increasingly popular resource among medical students, with many preferring ChatGPT over other traditional resources such as professors, textbooks, and lectures. Its impact on medical education will only continue to grow as its capabilities improve.